Cross-Cultural Dialogue: A Postcolonial Approach to Paul's Dialogue in Athens (Acts 17:16-34) - Tewu, Matulandi Arthur (Eduvest - Journal of Universal Studies, 2025)
This research explores Paul's speech in Athens (Acts 17:16-34) using a postcolonial lens to uncover how early Christian messaging engaged with dominant Greek cultural ideologies. The study aims to analyze how Paul positioned his message in the midst of a colonized cultural framework, focusing particularly on his use of local religious references, such as the "altar to the unknown God," to bridge theological narratives and cultural relevance. Employing a qualitative method grounded in textual and thematic analysis, the study draws from postcolonial theory, particularly the concepts of hybridity and cultural negotiation. Findings reveal that Paul’s approach at the Areopagus demonstrates a dialogical method of communication in which he neither rejected nor fully assimilated Athenian culture, but reinterpreted it through the lens of Christian theology. His strategy resulted in religious hybridity that allowed his message to be more accessible within the dominant Greco-Roman discourse. This study contributes to a broader understanding of intercultural dialogue in religious contexts and emphasizes the utility of postcolonial theory for interpreting early Christian texts. The implications highlight the continued relevance of adaptive and respectful engagement in cross-cultural religious communication, particularly in power imbalances and cultural hegemony settings.